2017
DOI: 10.1186/s12871-017-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of desflurane-remifentanil vs. Propofol-remifentanil anesthesia on arterial oxygenation during one-lung ventilation for thoracoscopic surgery: a prospective randomized trial

Abstract: BackgroundOne-lung ventilation during thoracic surgery frequently disturbs normal systemic oxygenation. However, the effect of anesthetics on arterial oxygenation during one-lung ventilation has not been well established in human study. In this clinical trial, we investigated whether a difference between desflurane-remifentanil and propofol-remifentanil anesthesia can be observed with regard to oxygenation during one-lung ventilation for thoracoscopic surgery.MethodsAdult patients with lung cancer, scheduled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Desflurane and propofol are the anesthetic agents most preferred due to their short-acting properties with a low blood-gas partition coefficient and low context-sensitive halftime, respectively. [19] An animal study revealed that desflurane depressed hypoxic pulmonary vasoconstriction in a dose-dependent manner and impaired oxygenation during OLV. [20] Chao et al [19] also indicated that the administration of propofolremifentanil TIVA might be a better choice in preventing hypoxemia during OLV compared with desflurane-remifentanil balanced anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desflurane and propofol are the anesthetic agents most preferred due to their short-acting properties with a low blood-gas partition coefficient and low context-sensitive halftime, respectively. [19] An animal study revealed that desflurane depressed hypoxic pulmonary vasoconstriction in a dose-dependent manner and impaired oxygenation during OLV. [20] Chao et al [19] also indicated that the administration of propofolremifentanil TIVA might be a better choice in preventing hypoxemia during OLV compared with desflurane-remifentanil balanced anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[19] An animal study revealed that desflurane depressed hypoxic pulmonary vasoconstriction in a dose-dependent manner and impaired oxygenation during OLV. [20] Chao et al [19] also indicated that the administration of propofolremifentanil TIVA might be a better choice in preventing hypoxemia during OLV compared with desflurane-remifentanil balanced anesthesia. Cardiac output, the arterial partial pressure of oxygen (PaO 2 ) and mixed venous PO 2 also decreased with desflurane inhalation, whereas perfusion of the non-ventilated lung and shunt fraction remained comparable with the propofol infusion in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe cardiovascular diseases, CHF, COPD, chest deformity, drug abuse, BMI > 35, and history of anticonvulsant agent consumption were excluded from the study. Considering a 95% confidence interval, 80% power, and based on a similar study (27), the minimum sample size in each group was calculated as 55 patients. Using a permuted block randomization, the enrolled patients were divided into two groups of propofol and sevoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of hypoxemia during OLV is mainly influenced by the increase in the shunt and dead space ( 4 ). In fact, pulmonary arteriovenous fistula due to the presence of unsaturated blood is the most important cause of hypoxemia during OLV; hypoxic pulmonary vasoconstriction (HPV) is the major physiological defense mechanism against shunting ( 5 , 6 ). Based on this mechanism, pulmonary perfusion deviates from the unvented area to the ventilated area of the lung, and thus the unsaturated blood shunt is reduced and the hypoxemia is improved ( 5 – 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The two main drug categories for the maintenance of anesthesia, including propofol (intravenous) and isoflurane (inhalational), are relatively new anesthetics that have rapid onset and offset due to low blood/gas partition coefficient and context-sensitive half-life. However, their effect on HPV and subsequently on partial pressures of oxygen (PaO2), carbon dioxide (PaCO2), and end-tidal carbon dioxide (ETCO2) has not yet been well studied ( 2 , 5 , 6 , 12 ). Although it seems that the vasoconstrictive effect of inhalational anesthetics can affect the protective role of HPV and may interfere with the oxygenation during the OLV, the recent studies on the effect of inhalational and intravenous anesthetics on PaO2 have revealed contradictory findings (5, 13 and 14).…”
Section: Introductionmentioning
confidence: 99%